2011
DOI: 10.1002/cphc.201100630
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Spin‐Labeling of Polymers for Enhancing NMR Sensitivity by Solvent‐Free Dynamic Nuclear Polarization

Abstract: Dynamic nuclear polarization (DNP) [1] combined with magic angle spinning (MAS) [2] can-under favorable conditions-enhance the nuclear spin polarization, that is, the difference between the populations of the Zeeman levels j ai and j bi of a spin I = 1 = 2 by up to two orders of magnitude (e DNP 10 2 ) with respect to the Boltzmann distribution at thermal equilibrium at ca. 100 K, while accelerating relaxation and hence reducing recovery delays by more than an order of magnitude (k = R DNP / R 1 = T 1 /t DNP >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 21 publications
2
88
0
Order By: Relevance
“…This solvent-free DNP procedure demonstrated here for materials exhibits similarities with another solvent-free DNP protocol, which has been introduced recently for the DNP of polypeptides [31]. In this work, the molecular entities, unlabeled and labeled with nitroxide radicals, are cocondensed, whereas in reference [31], they were mixed by dissolution and solvent evaporation. In this article, the results of 1 H and 29 Si DNP experiments will be presented for 1 obtained using co-condensation.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This solvent-free DNP procedure demonstrated here for materials exhibits similarities with another solvent-free DNP protocol, which has been introduced recently for the DNP of polypeptides [31]. In this work, the molecular entities, unlabeled and labeled with nitroxide radicals, are cocondensed, whereas in reference [31], they were mixed by dissolution and solvent evaporation. In this article, the results of 1 H and 29 Si DNP experiments will be presented for 1 obtained using co-condensation.…”
Section: Introductionmentioning
confidence: 83%
“…This co-condensation procedure can be advantageous, since: (i) it can be applied in principle to nonporous materials or microporous materials exhibiting pore aperture smaller than the smallest dimension of TEMPO and TOTAPOL (about 7 Å ); (ii) it ensures a more homogeneous distribution of organic moieties within the inorganic material than post-synthesis incorporation [30]; (iii) the distance between the unpaired electrons and the silica surface cannot exceed 9 Å , the size of the organic moiety; (iv) this hybrid material allows solvent-free DNP to be tested since the xerogels are dried during the sample preparation [24]. This solvent-free DNP procedure demonstrated here for materials exhibits similarities with another solvent-free DNP protocol, which has been introduced recently for the DNP of polypeptides [31]. In this work, the molecular entities, unlabeled and labeled with nitroxide radicals, are cocondensed, whereas in reference [31], they were mixed by dissolution and solvent evaporation.…”
Section: Introductionmentioning
confidence: 88%
“…When the buildup time and T 1 are different, as seen in Figures 4 and 5, a better measure of the improvement in signal-to-noise ratio is sensitivity (S/N*t −1/2 ) rather than enhancement, which in this case is a factor of 128. (One may take more factors into account when calculating improvements from DNP, such as dilution of the sample and bleaching due to the electron spin, as done recently by Jannin et al 69 ) To our knowledge, this is the best gain in sensitivity reported for contemporary DNP experiments using the solid effect with 1 H enhancement at high fields (5 T). Additionally, we see in Figure 6 that as we increase the microwave field strength, we do not yet observe evidence of saturation of the solid effect.…”
Section: Methodsmentioning
confidence: 98%
“…Such SDSL techniques are widely applied in PRE studies. They have also been used in recent liquidstate DNP work [18,19], and may become attractive for solid-state DNP [20]. Once a protein or nucleic acid is spin labeled, further information can be obtained from CW EPR experiments [14] or distance measurements between spin labels by pulsed EPR techniques [21].…”
Section: Introductionmentioning
confidence: 99%